Artificial marble and preparation method thereof

By using solid waste and alum stone calcined material as reinforcing agents, combined with composite additives and negative pressure stirring technology, the problems of dependence on silicate cement and poor durability of artificial marble were solved, and high-strength, low-carbon, large-volume artificial marble was prepared.

CN121135334APending Publication Date: 2025-12-16YANCHENG INST OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511302868.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

Existing artificial marble technology is highly dependent on silicate cement, which leads to problems such as high carbon emissions, efflorescence, and poor durability, and makes it difficult to produce large-volume, high-strength products.

Method used

Using solid waste as the main raw material, low-volume silicate cement and calcined alum stone as a reinforcing agent, combined with a composite additive of polycarboxylate superplasticizer and polyether defoamer, a dense micro-network structure is formed through negative pressure stirring and vibration molding process.

Benefits of technology

It achieves low-carbon and environmentally friendly high-strength artificial marble with a compressive strength exceeding 80MPa and a flexural strength exceeding 10MPa. It avoids alkali return and the durability problems of organic materials, and can produce large-volume, high-quality products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121135334A_ABST
    Figure CN121135334A_ABST
Patent Text Reader

Abstract

The invention discloses artificial marble and a preparation method thereof, and the artificial marble comprises the following components in percentage by mass: 20.00%-29.00% of mineral powder, 0.00%-3.60% of I-grade fly ash, 2.80%-5.40% of desulfurized gypsum, 0.28%-1.80% of Portland cement, 0.14%-0.72% of a reinforcing agent, 0.22%-0.54% of a composite additive, 55.92%-65.68% of sand and 5.04%-7.20% of water, the composite admixture is a compound of a polycarboxylic acid water reducer and a polyether defoaming agent, the artificial marble with extremely low porosity and high strength is prepared through negative pressure stirring, vibration forming and curing, the compressive strength of 28 days is larger than 80 MPa, and the breaking strength is larger than 10 MPa. The invention relates to a high-performance inorganic artificial stone material which is obtained by fully utilizing a slag gelling system of a sulfate activator and modifying with calcined alunite.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a kind of building decoration materials, especially to a kind of artificial marble with solid waste as main raw material, and its preparation method with very low cement consumption. BACKGROUND

[0002] Artificial marble, as an important building decoration material, is facing the triple challenges of carbon emission, primary resource consumption and solid waste pollution. The traditional artificial marble is highly dependent on ordinary Portland cement (OPC), which has the problems of large-scale mining of natural stone, large emission of carbon dioxide and limited performance in the production process. In order to improve the performance, various improvement attempts have been made in the prior art. For example, resin-based artificial stone, which uses organic polymer as adhesive, Chinese invention patent with application number CN201510012318.6 discloses a product made of particle sand 15-50%, stone waste 10-35%, glue 2-8%, unsaturated resin 10-20%, curing agent 0.8-2%, accelerator 0-2%, pigment 0-2% and calcium carbonate 40-50%; Chinese invention patent with application number CN202510083968.3 uses acrylic monomer, polyurethane acrylate, etc. as the core bonding material. This technical route has fundamental defects: (1) it is difficult to treat wastewater containing resin; (2) the long-term durability, weather resistance and aging resistance of organic resin are far inferior to those of inorganic materials, and yellowing, cracking and other problems are prone to occur; (3) the complex organic-inorganic composite material structure makes it difficult to separate and recycle after disposal, causing secondary pollution. Chinese invention patent with application number CN89105654.8 discloses an inorganic artificial marble using high-alumina cement as the main cementitious material, with a ratio of high-alumina cement 100 parts, aggregate 30-250 parts, pigment 0-20 parts, triethanolamine 1.5-5 parts, glycerol 1.5-5 parts, calcium chloride 1.5-5 parts, water 35-60 parts. The high-alumina cement hydration product is a metastable mineral, which will lose gloss and lose its decorative effect after years of use, and the overall strength will also decrease. In addition, the chloride ions in this technology are prone to migrate to the surface of the product and absorb moisture, causing surface whitening and frosting. Chinese patent with application number CN202311428884.6 discloses an inorganic artificial marble made of dihydrate gypsum as the main raw material, including dihydrate gypsum 500-950 parts, mineral powder 150-400 parts, cement 50-200 parts, polycarboxylic acid water reducer 1-5 parts, cellulose 0.1-1 parts, water glass 1-2 parts, redispersible latex powder 1-6 parts, graphene 0.1-1 parts, and aggregate 1000-3000 parts. This technology still has a lot of dihydrate gypsum after the concrete hardens, and the performance will decrease in a humid environment or water for a long time. Although the addition of latex powder can improve the waterproofness, it is easy to produce macroscopic bubbles during preparation, and the addition of water glass and graphene increases the cost and has the tendency of efflorescence.A Chinese invention patent with application number CN202410798878.8 discloses a method for manufacturing artificial marble by using a cementitious material system formed by the reaction of light-burned magnesium oxide and magnesium sulfate solution. The ratio is 24.0%-30.0% light-burned magnesium oxide, 9.0%-12.0% magnesium sulfate, 1.0%-2.0% microsilica powder, 6.2%-11.74% quartz sand, 12.0%-18.0% matte black stone, 10.0%-16.0% bright black stone, 6%-10% light gray stone, 5.0%-8.0% white stone, 0.05%-0.10% citric acid, 0.05%-0.10% water reducing agent, 0.05%-0.10% defoaming agent, 0.5%-1.0% polymer powder, 0.5%-1.0% pigment, and 8.0%-12.0% water. The water resistance is improved by adding microsilica powder and polymer powder, but the water resistance of the hydration product is not fundamentally changed, and the cost is high. A Chinese invention patent with application number CN201910442501.8 uses ultra-high performance concrete (UHPC) technology. The ratio includes 525 white Portland cement 100 parts, silica fume 8 parts, slag powder 20 parts, 4-6 mesh yellow rice stone 60 parts, 4-6 mesh black rice stone 20 parts, 10-20 mesh yellow rice stone 50 parts, 40-80 mesh white rice stone 20 parts, 80-120 mesh quartz powder 5 parts, 800-1200 mesh quartz powder 5 parts, polycarboxylic acid superplasticizer 0.8 parts, hydrophobic powder 0.6 parts, iron oxide yellow pigment 2 parts, fly ash 10 parts, nano titanium dioxide 1 part, nano silicon dioxide 1.5 parts, and nano calcium carbonate 2.5 parts. This technology is highly dependent on high-strength grade special cement, and the cement content is 32.7% of the total dry material mass. There are also various nanomaterials, resulting in a large carbon footprint and high material cost. The characteristic of the preparation process is that the slurry is injected into the mold, and then vacuum is applied during the pressing process to remove excess water and bubbles, obtaining high-strength artificial marble products. However, due to the vacuum during the pressing process, only thin products can be prepared. A Chinese invention patent with application number CN202111285166.9 attempts to use roller compaction to prepare artificial marble. The formulation is 15-20% cement, 0-30% fly ash, and 55-80% slag. The cement content is as high as 15-20%, and the performance of slag fluctuates greatly with high water absorption. The water-binder ratio is between 0.3 and 0.4, and the product stability is very poor. In addition, this scheme can only prepare thin products and cannot prepare large-volume blocks. A Chinese invention patent with application number CN202010295823.7 improves the toughness of inorganic concrete by polymer modification, including white cement 6-8 parts, calcium powder 20-25 parts, metakaolin 2-4 parts, quartz sand, latex powder 8-12 parts, and fiber, etc. This scheme improves the toughness, but the introduction of more organic matter such as latex powder still has problems such as performance decline after aging, surface color deterioration, etc.

[0003] In addition, there are high-temperature melting / sintering, which melts and crystallizes various wastes by high-temperature heat treatment, and converts them into glass ceramics or cast stone materials with excellent performance. The Chinese invention patent with application number CN200410011538.9 describes a process for utilizing garbage incineration fly ash: mixing fly ash with additives, melting at a high temperature of 1300-1500 DEG C, and then crystallizing by controllable cooling. Although the product has excellent performance, its huge energy consumption makes its production cost high, which seriously limits its large-scale low-carbon production. SUMMARY

[0004] Invention purposes: The purpose of the present application is to reduce the dependence of artificial marble on Portland cement, avoid the "back alkali" phenomenon and poor durability, and improve the density and strength of marble. The present application provides an artificial marble which uses solid waste as the main raw material and has a very low cement dosage. Another purpose of the present application is to provide a preparation method of the artificial marble.

[0005] Technical scheme: The artificial marble according to the present application comprises, by mass percentage, 20.00-29.00% of mineral powder, 0.00-3.60% of I-grade fly ash, 2.80-5.40% of desulfurization gypsum, 0.28-1.80% of Portland cement, 0.14-0.72% of a reinforcing agent, 0.22-0.54% of a composite admixture, 55.92-65.68% of sand, and 5.04-7.20% of water, which are mixed, negatively stirred, vibration-molded, and cured to obtain the artificial marble. The composite admixture is a compound of polycarboxylate superplasticizer and polyether defoamer.

[0006] Further, the polycarboxylate superplasticizer accounts for 94.12-99.67% of the composite admixture, and the polyether defoamer accounts for 0.33-5.88%. The superplasticizer is a viscosity-reducing polycarboxylate superplasticizer with a solid content of 22%. The polycarboxylate superplasticizer forms a non-bridging adsorption layer with steric hindrance and / or electrical repulsion on the surface of the particles, which makes the particles disperse, reduces the structured network, and thus reduces the yield stress and plastic viscosity of the slurry, promotes the dispersion of the mineral powder, fly ash, cement, and desulfurization gypsum in the system, reduces the water consumption, and maintains the fluidity of the system and improves the mixing uniformity with a suitable water-binder ratio. A small amount of polyether defoamer reduces the surface tension, destroys the stability of the bubbles, and reduces the generation of bubbles in the mixing system. On the basis of chemical defoaming, negative pressure stirring and vibration molding are further used to eliminate the bubbles in the marble, overcome the problem that the common chemical defoaming and negative pressure molding are only suitable for bubble removal of thin-walled products, achieve efficient defoaming of macroscopic bubbles in large-volume products, and obtain a marble with a higher yield, better appearance, and higher hardness.

[0007] Further, the reinforcing agent is a mixture of calcined alunite at 500-580 DEG C, and the chemical composition in terms of mass fraction of oxides is: potassium oxide 9.8-12.4%, aluminum oxide 35.7-40.2%, sulfur trioxide 37.3-41.3%, iron oxide and other impurities 3.5-8.7%. The reinforcing agent contains high-activity aluminum oxide, which can accelerate the formation of ettringite; contains a small amount of potassium ions, which is conducive to the rapid activation of the activity of the mineral powder, and the rapid generation of hydrated aluminosilicate minerals; in addition, the remaining part of the sulfate ions is also an activity activator of the slag, and in combination with a small amount of portland cement and a higher amount of gypsum as the activator of the mineral powder, the potential activity of the mineral powder is activated, the reaction activity and reaction rate are improved, the problem of insufficient early strength of the low portland cement (0.28%-1.80%) system is solved, and the efflorescence phenomenon is prevented due to the low potassium content and the hydration into aluminosilicate.

[0008] Further, the specific surface area of the blast furnace mineral powder is 500-700 m 2 / kg, the specific surface area of the desulfurization gypsum is 250-300 m 2 / kg, the specific surface area of the I-grade fly ash is 450 m 2 / kg or more, and the specific surface area of the portland cement is 300-350 m 2 / kg, and the strength grade is 42.5 or more. The greater the specific surface area, the greater the contact area between the components, the faster and more complete the dissolution, and the higher the utilization rate of the solid waste. The dependence of the solid waste dissolution on the activator and the amount of the activator is reduced, and the amount of cement is greatly reduced, thereby greatly solving the dependence of the artificial marble on the portland cement and greatly promoting the green and low-carbon development of the artificial marble.

[0009] Further, the sand is machine-made fine sand, the fineness modulus is 2.2-3.5, the void ratio is not more than 44%, and the crushing value is not more than 9%. The performance of the fine aggregate plays a decisive role in the high polishing effect and mechanical properties of the artificial marble. The uniformly distributed fine sand makes the polishing performance of the artificial marble good and reduces stress concentration, and the hardness, thickness and aesthetics can be considered.

[0010] The application provides a preparation method of the artificial marble.

[0011] (1) mixing the mineral powder, the I-grade fly ash, the desulfurization gypsum, the portland cement and the reinforcing agent to prepare a cementitious material;

[0012] (2) mixing the cementitious material with the sand to prepare a mixture;

[0013] (3) adding water and a composite admixture and mixing and stirring for 30-60 s;

[0014] (4) 0.01-0.05 MPa negative pressure conditions under stirring 10-30 s;

[0015] (5) Pour into the mold, and then vibrate at a vibration frequency of 3000-4500 times / min;

[0016] (6) After 1 day of mold curing, demold and continue curing for not less than 28 days.

[0017] Further, the fluidity of the mixture is not less than 200 mm, the water-binder ratio is controlled in a smaller range of 0.18-0.21, the water consumption is reduced as much as possible while the slurry forming performance is ensured, so as to avoid the adverse effects on the strength and appearance quality of the finished product, the curing temperature is not less than 20℃, and the relative humidity is not less than 90%, the marble prepared by the above method has a 28-day compressive strength of not less than 80 MPa and a 28-day flexural strength of not less than 10 MPa.

[0018] Advantages: Compared with the prior art, the present application has the following remarkable advantages: 1. Industrial solid waste is used as the main raw material to generate stable ettringite, hydrated calcium silicate gel and hydrated aluminosilicate and other hydration products, and a dense micro network structure is formed by filling each other under low water-binder ratio, so that the marble has good compactness, high strength and good durability, and the durability problems such as yellowing and strength attenuation caused by aging and ultraviolet radiation of organic resin are avoided; 2. The mixture obtained by calcining alunite is used as a reinforcing agent, a small amount of portland cement and a high amount of gypsum are used as a mineral powder activator, the dependence on portland cement is reduced, the amount of portland cement is sharply reduced to the limit level of 0.28%-1.80%, the manufacturing cost is reduced, the potential activity of the mineral powder is activated by the reinforcing agent to improve the reaction activity and reaction rate, and thus the strength of the material is improved, and a small amount of potassium ions are solidified in the crystal structure of the hydration product to avoid the "back-alkali" phenomenon caused by surface precipitation; 3. The dense microstructure of the cementitious matrix reduces ion migration and thus reduces the probability of surface salt precipitation, the good compactness prevents water from carrying soluble ions to the surface through capillary pores to combine with CO2 in the air, and thus the "back-alkali" phenomenon is further avoided; 4. The internal macropores of the mixture are reduced by the combination of the composite admixture and negative pressure stirring, and the porosity of the final product is extremely low, and thus the strength of the artificial marble is further improved, which can be comparable to the hardness and wear resistance of natural stone, the 28-day compressive strength is greater than 80 MPa, and the 28-day flexural strength is greater than 10 MPa, which is better than the preparation scheme of pouring the slurry into the mold after stirring the mixture and then vacuumizing and exhausting; 5. The inorganic material is prepared at room temperature, the huge energy consumption of high-temperature sintering process and the problems of separation and recycling in the later stage are avoided, and green production is realized. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 A marble product prepared by the present application. DETAILED DESCRIPTION

[0020] The technical solutions of the present application are further described below in combination with examples and drawings. The mineral powder with a specific surface area of 500-700 m 2 / kg, desulfurization gypsum with a specific surface area of about 250-300 m 2 / kg, Portland cement with a specific surface area of 300-350 m 2 / kg, and Grade I fly ash with a specific surface area of 450 m 2 / kg or above are selected to prepare the cementitious material; the machine-made fine sand has a void ratio of ≤44%, a crushing value of ≤9%, and a fineness modulus of 2.2-3.5.

[0021] Example 1

[0022] A method for preparing an artificial marble includes the following steps in terms of mass percentage:

[0023] (1) Preparing the cementitious material: 24.00% of the mineral powder, 2.40% of Grade I fly ash, 5.40% of desulfurization gypsum, 1.80% of Portland cement, and 0.60% of the reinforcing agent are mixed to form the cementitious material;

[0024] (2) Preparing the mixture: the cementitious material and 59.76% of the machine-made fine sand are mixed to obtain the mixture;

[0025] (3) Mixing: 0.54% of the composite admixture and 5.50% of water are added to the mixture, the water-binder ratio (the mass ratio of water to the cementitious material) is controlled to be 0.18, and the mixture is stirred and mixed at a rotating speed of 300 r / min for 3 min, wherein the composite admixture is composed of 98.00% of the polycarboxylate-based water reducing agent and 2.00% of the polyether-based defoaming agent;

[0026] (4) Negative pressure stirring: the mixture is transferred to a vacuum stirrer, stirred at a negative pressure of 0.05 MPa for 20 s, and the excess air bubbles in the mixture are removed to improve the density;

[0027] (5) Vibration forming: the mixture is loaded into a 40 mm x 40 mm x 160 mm prismatic mold or a 100 mm x 100 mm x 100 mm cubic mold, vibration compaction is performed at a vibration frequency of 4000 times / min for about 20 s, and the mixture is vibrationally compacted and formed;

[0028] (6) Curing: after being cured in the mold for 1 day, the mixture is demolded and cured for not less than 28 days, the curing temperature is not less than 20℃, and the relative humidity is not less than 90%.

[0029] Example 2

[0030] Different from example 1, the artificial marble includes mineral powder 22.00%, I-class fly ash 3.60%, desulfurization gypsum 3.20%, Portland cement 1.80%, reinforcing agent 0.72%, fine machine-made sand 63.10%, composite admixture 0.54% and water 5.04% by mass percentage, the water-binder ratio is controlled to be 0.18, the composite admixture is composed of 96.50% polycarboxylate superplasticizer and 3.50% polyether defoaming agent, and the preparation method refers to example 1.

[0031] Example 3

[0032] Different from example 1, the artificial marble includes mineral powder 29.00%, desulfurization gypsum 5.40%, Portland cement 1.80%, reinforcing agent 0.14%, fine machine-made sand 55.92%, composite admixture 0.54% and water 7.20% by mass percentage, the water-binder ratio is controlled to be 0.21, the composite admixture is composed of 94.12% polycarboxylate superplasticizer and 5.88% polyether defoaming agent, and the preparation method refers to example 1.

[0033] Example 4

[0034] Different from example 1, the artificial marble includes mineral powder 29.00%, I-class fly ash 1.50%, desulfurization gypsum 2.80%, Portland cement 0.28%, reinforcing agent 0.72%, fine machine-made sand 59.02%, composite admixture 0.22% and water 6.46% by mass percentage, the water-binder ratio is controlled to be 0.20, the composite admixture is composed of 99.67% polycarboxylate superplasticizer and 0.33% polyether defoaming agent, and the preparation method refers to example 1.

[0035] Example 5

[0036] Different from example 1, the artificial marble includes mineral powder 29.00%, desulfurization gypsum 5.40%, Portland cement 1.00%, reinforcing agent 0.60%, fine machine-made sand 57.40%, composite admixture 0.32% and water 6.28% by mass percentage, the water-binder ratio is controlled to be 0.18, the composite admixture is composed of 95.50% polycarboxylate superplasticizer and 4.50% polyether defoaming agent, and the preparation method refers to example 1.

[0037] Example 6

[0038] Different from example 1, the artificial marble comprises, in mass percentage, 20.00% of mineral powder, 5.40% of desulfurized gypsum, 1.80% of portland cement, 0.72% of reinforcing agent, 65.68% of fine machine-made sand, 0.54% of composite admixture, and 5.86% of water, the water-binder ratio is controlled to be 0.21, wherein the composite admixture is composed of 97.50% of polycarboxylic acid type water reducing agent and 2.50% of polyether type defoaming agent, and the preparation method refers to example 1.

[0039] Comparative example 1

[0040] Compared with example 1, the composition does not add reinforcing agent, the fine machine-made sand is 60.49%, the water is 5.37%, the water-binder ratio is unchanged, and the remaining solid components are the same as those in example 1. The technical indexes of the raw materials used refer to example 1, and the preparation process refers to example 1.

[0041] Comparative example 2

[0042] Compared with example 1, the composite admixture has the same dosage, but all is polymeric carboxylic acid water reducing agent, and no polyether type defoaming agent is added. The technical indexes of the raw materials used refer to example 1, and the preparation process refers to example 1.

[0043] Comparative example 3

[0044] Compared with example 1, the composition has the same composition, and the technical indexes of the raw materials used refer to example 1. In the preparation process, step (4) is stirred at normal pressure for 20 seconds, and the remaining preparation steps (pre-mixing, mold filling, vibration, demolding after 1 day of in-mold curing, and placing in a curing room for 28 days) are the same as those in example 1.

[0045] To systematically optimize the components of the present application and clarify the mechanism, the mechanical property tests of all examples and comparative examples of the present application are strictly carried out according to the current national standard. According to GB / T 2419-2005 “Cement mortar fluidity test method”, the fluidity is 220 mm, and the fluidity meets the requirements of claim 6. The test method for flexural strength test is carried out according to GB / T 17671-2021 “Cement mortar strength test method (ISO method)”; the test method for compressive strength test is carried out according to GB / T 50081-2019 “Standard for test methods of physical and mechanical properties of concrete”, and the test results are shown in table 1.

[0046] Table 1: Determination results of flexural strength and compressive strength of artificial marble at 3 days and 28 days

[0047]

[0048] Compared with Comparative Example 1-6, the amount of Portland cement is only 0.28%-1.80%, which breaks the dependence of artificial marble on Portland cement; the amount of reinforcing agent is 0.14%-0.72%, which is combined with composite admixture and negative pressure stirring forming process under the condition of low water-binder ratio, and a kind of artificial marble with low cost and excellent performance is successfully prepared, which shows significant early (3 days) and long-term (28 days) mechanical performance advantages. Especially in Example 1, the 28-day compressive strength is as high as 93.2 MPa, which realizes the significant improvement of material performance. In contrast, Comparative Example 1 (without reinforcing agent) shows obvious insufficient early and late strength, with a decrease of about 14.0% in 3-day compressive strength and a decrease of about 15.0% in 28-day compressive strength, which indicates that the reinforcing agent plays a reinforcing role in activating the potential activity of the mineral powder, and its absence leads to a decrease in the efficiency of cementation reaction and an increase in porosity, which significantly weakens the mechanical properties of the material; Comparative Example 2 does not add polyether defoaming agent, and compared with Example 1, the 3-day flexural strength decreases by about 13.0%, the compressive strength decreases by about 14.8%, the 28-day flexural strength increases by about 21.5%, and the compressive strength increases by about 8.7%, which indicates that the absence of defoaming agent in the reinforcing agent will lead to an increase in the residual air bubbles in the mixture, which reduces the density of the material and thus has a negative impact on the mechanical properties; Comparative Example 3 uses normal pressure stirring instead of vacuum stirring, and compared with Example 1, the 3-day flexural strength decreases by about 23.2%, the compressive strength decreases by about 16.9%, the 28-day flexural strength increases by about 30.8%, and the compressive strength increases by about 19.3%, which shows that normal pressure stirring cannot effectively remove the large air bubbles in the mixture, and the porosity of the product is larger than that of negative pressure stirring, which further reduces the early and long-term strength of artificial marble.

[0049] Compared with resin-based artificial marble, the use of pure inorganic system avoids the durability problems such as yellowing and strength decay caused by factors such as aging and ultraviolet radiation; compared with high-alumina cement-based marble, it overcomes the problem that high-alumina cement is prone to crystal transformation, and the decorative and strength properties deteriorate over time; compared with magnesium-based cement artificial marble, it overcomes the water resistance problem and reduces the manufacturing cost; compared with Portland cement-based artificial marble, it overcomes the high carbon emission of inorganic artificial stone prepared by Portland cement; compared with gypsum-based artificial marble, calcined alunite replaces water glass, avoiding the risk of late efflorescence caused by the strong alkali residue of water glass, improving the long-term use stability of the product, and the sulfate in the invention is basically consumed during the reaction with the mineral powder, and the hydration product is a hydraulic material, avoiding the defect that gypsum-based artificial marble is prone to dissolution and may reduce the long-term durability.

[0050] The present application overcomes the problems of easy alkali, poor durability, high cost and low carbon in the prior art by precisely controlling the proportion of components such as mineral powder, desulfurized gypsum, a small amount of cement and fine sand, and using the mixture obtained by calcining alunite as a reinforcing agent. A low-viscosity water reducing agent is used in combination with a small amount of defoaming agent, and on the basis of chemical defoaming, negative pressure stirring is used in the stirring process, followed by pouring and forming, which improves the defoaming efficiency, realizes the preparation of artificial stone without macroscopic defects, and can produce relatively thick and large-volume artificial marble. The negative pressure process is moved to the stirring process, and the bubbles, especially large bubbles, are removed in the dynamic processes such as slurry tumbling and convection. Compared with the negative pressure forming process, the problems of large resistance in the process of escaping bubbles from the bottom layer and the difficulty of removing multiple bubbles are avoided, the problem of negative pressure forming only being suitable for thin-walled products is overcome, the bubble removal efficiency is greatly improved, and through the process principle of mutual synergy defoaming of chemical defoaming and negative pressure stirring, the bubbles in the slurry are effectively removed, laying a solid foundation for obtaining homogeneous and dense internal structure of artificial stone. Different shapes or sizes of artificial stone products can be obtained through simple pouring and forming.

Claims

1. An artificial marble, characterized in that, The product comprises, by weight percentage, 20.00%-29.00% mineral powder, 0.00%-3.60% Grade I fly ash, 2.80%-5.40% desulfurized gypsum, 0.28%-1.80% silicate cement, 0.14%-0.72% reinforcing agent, 0.22%-0.54% composite admixture, 55.92%-65.68% sand, and 5.04%-7.20% water, and is prepared by mixing, negative pressure stirring, vibration molding, and curing; the composite admixture is a compound of polycarboxylate superplasticizer and polyether defoamer.

2. The artificial marble according to claim 1, characterized in that, The composite admixture comprises 94.12%-99.67% polycarboxylate superplasticizer and 0.33%-5.88% polyether defoamer.

3. The artificial marble according to claim 2, characterized in that, The polycarboxylate superplasticizer has a solid content of 22%.

4. The artificial marble according to claim 1, characterized in that, The reinforcing agent is a mixture obtained by calcining alunite, and its chemical composition, based on the mass fraction of oxides, is as follows: potassium oxide 9.8-12.4%, aluminum oxide 35.7-40.2%, sulfur trioxide 37.3-41.3%, and iron oxide and other impurities 3.5-8.7%.

5. The artificial marble according to claim 1, characterized in that, The specific surface area of ​​the mineral powder is 500-700 m². 2 / kg, the specific surface area of ​​desulfurized gypsum is 250-300m² 2 / kg, the specific surface area of ​​Grade I fly ash is 450m² 2 / kg or more.

6. The artificial marble according to claim 1, characterized in that, The specific surface area of ​​the silicate cement is 300-350 m². 2 / kg, with a strength grade of 42.5 or higher.

7. The artificial marble according to claim 1, characterized in that, The sand is a high-quality manufactured sand with a fineness modulus of 2.2-3.5, a porosity of no more than 44%, and a crushing value of no more than 9%.

8. A method for preparing artificial marble according to any one of claims 1-7, characterized in that, Includes the following steps: (1) Mix mineral powder, Class I fly ash, desulfurized gypsum, silicate cement and reinforcing agent to prepare cementitious materials; (2) Mix the cementitious material with sand to prepare a mixture; (3) Add water and compound additives and mix for 30-60 seconds; (4) Stir for 10-30 seconds under a negative pressure of 0.01-0.05 MPa; (5) Pour into a mold and then vibrate to form at a vibration frequency of 3000 to 4500 times / min; (6) After curing in the mold for 1 day, demold and continue curing for no less than 28 days.

9. The method for preparing artificial marble according to claim 8, characterized in that, In step (6), the curing temperature shall not be less than 20°C and the relative humidity shall not be less than 90%.

10. The method for preparing artificial marble according to claim 8, characterized in that, The compressive strength after 28 days is not less than 80 MPa, and the flexural strength after 28 days is not less than 10 MPa.

Citation Information

Patent Citations

  • Artificial cement marble and making method thereof

    CN1044082A

  • Energy-saving high-performance artificial stone and preparation method thereof

    CN104556823A

  • Cement-based ultra-high performance artificial stone slabs

    CN110550902B

  • High-toughness cement-based artificial stone formula and preparation method

    CN111574144A

  • Method for preparing high-strength artificial marble by exciting and activating low-calorific-value coal ash slag

    CN113954203A